1989
DOI: 10.1007/bf01799331
|View full text |Cite
|
Sign up to set email alerts
|

The control of 5‐hydroxytryptamine and dopamine synthesis in the brain: A theoretical approach

Abstract: The transport of the eight amino acids (phenylalanine, tyrosine, tryptophan, valine, leucine, isoleucine, histidine and methionine) using the large neutral amino acid transporter of the blood-brain barrier (BBB) has been calculated using published kinetic data. The fate of the amino acids has been followed from blood to interstitial space, to cell and through metabolism which included, for tyrosine and tryptophan, the hydroxylases. The system was analysed in terms of flux control coefficients. Since the summat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Theoretical calculations of brain amino acid fluxes in PKU, based on estimated plasma amino acid concentration and on experimentally determined Vma x and K m values, have previously been carried out (Hommes 1989;Hommes and Lee 1990a). In those studies it was concluded that effects at the BBB could not provide an entire explanation for the aetiology of brain damage, since similar Completion effects take place in histidinaemia and tyrosinaemia, type II, where brain dysfunction does not develop to the same extent.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical calculations of brain amino acid fluxes in PKU, based on estimated plasma amino acid concentration and on experimentally determined Vma x and K m values, have previously been carried out (Hommes 1989;Hommes and Lee 1990a). In those studies it was concluded that effects at the BBB could not provide an entire explanation for the aetiology of brain damage, since similar Completion effects take place in histidinaemia and tyrosinaemia, type II, where brain dysfunction does not develop to the same extent.…”
Section: Discussionmentioning
confidence: 99%
“…High brain Phe concentrations have been found to be neurotoxic and to affect brain metabolism [ 10 14 ], while reduced brain availability of non-Phe LNAA has been related to impaired cerebral protein synthesis [ 6 , 15 ]. In addition, impaired cerebral monoaminergic neurotransmitter synthesis may result from outcompeted brain uptake of their amino acid precursors tyrosine and tryptophan [ 16 ], and/or from an inhibitory effect of high brain Phe concentrations on tyrosine hydroxylase (TH) and tryptophan hydroxylase (TPH) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent calculations on the control of tyrosine hydroxylase and tryptophan hydroxylase in brain have shown that the supply of substrates for these enzymes as well as the flux through these enzymes is largely controlled by the phenylalanine level and that the transport across the BBB does not contribute to the cause of permanent brain dysfunction in PKU (Hommes, 1989;Hommes and Lee, 1990). These calculations raised the question as to whether increased plasma concentrations of VIL could modify the flux through the hydroxylases or lower the brain phenylalanine levels to therapeutically acceptable levels.…”
mentioning
confidence: 99%